Pain assessment in the Emergency Department. Correlation between pain rated by the patient and by the nurse. An observational study - Giusti, Gian Domenico; Reitano, Bianca; Gili, Alessio (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the study: Pain is always present in the Emergency Department (ED), but is often underestimated. The primary purpose of this study is to analyze the degree to which the intensity of pain is underestimated or overestimated in the perception of the nurse and the patient in the ED. The secondary objective of this research is to study possible factors that lead to these discrepancies in assessment. Methods: The observational study was carried out in two Hospitals in Central Italy. The sample population was based on 130 patients and 26 nurses. A questionnaire was given to the patients who provided personal data followed by information regarding their pain, including an assessment of the intensity of pain on a scale from 0 to 10. A similar questionnaire was given to the nurses. Results: The average score based on the numeric rating scale (NRS) to assess the intensity of pain perceived by the patients is 6.16, while the numerical average estimated by the nurses based on their assessment is 5. Using the t test we found that the average between nurse and patient assessments was very significant. The analysis of the nurses’ characteristics and professional experiences, age, years of employment and years of service in the ED are all significant variables affecting the discrepancy between the nurses’ and patients’ assessments of pain. As previous studies have shown, nurses tend to underestimate the degree of pain. In fact, in only 55.5% of the cases was there a correspondence in the evaluations of the intensity of pain done by nurses and patients, and in no case did the nurses’ evaluation exceed that of the patients. Conclusions: This study reveals the persistent difficulty in pain management, while attempting contemporaneously to communicate the importance of the assessment, since adequate understanding of pain renders it possible to recognize and treat it.